Sing to the Lord a New Song: John Calvin and the Spiritual Discipline of Metrical Psalmody - Brandon J. Bellanti (Musical Offerings, 2014)
The purpose of this essay is to evaluate the way that psalmody - specifically metrical psalmody - serves as a sort of spiritual discipline. In other words, this essay seeks to demonstrate how the singing of psalms can be a tool to aid in spiritual growth. Much of the research for this essay focuses on the theological writings of the Protestant reformer John Calvin, as well as the way in which he incorporated metrical psalmody into his liturgical framework. The research also comprises primary writings from Aristotle, Plato, Saint John Chrysostom, Saint Basil, and Saint Augustine - all of whom influenced Calvin’s own philosophy regarding the use of art, music, and psalmody in worship.